PELATIHAN PENGGUNAAN MEDIA E-KOMIK DALAM PEMBELAJARAN MATEMATIKA DI SMP - Ratna Rustina; Ipah Muzdalipah; Edi Hidayat (Universitas Bina Taruna Gorontalo, 2024)
This service aims to improve teachers' skills in using e-comic media as a mathematics learning aid at SMPN 1 Banjar. This training is designed to provide teachers with practical understanding and skills in creating and integrating e-comics into the learning process. The methods used in this training include workshops, group discussions, and direct practice. The training participants consisted of 20 mathematics teachers from various grade levels. Training evaluation is carried out through observations, interviews and questionnaires given before and after training. The evaluation results show a significant increase in teachers' abilities in creating and using e-comics as a learning medium. Teachers also reported increased student interest and involvement in mathematics learning after using e-comic media. In conclusion, this training succeeded in increasing teacher competency in using digital technology for learning, and it is hoped that it can be widely applied to improve the quality of mathematics education in other schools.